Analysis of Effective Operation Performance of Wireless Control Downhole Choke. (12th November 2020) - Fu, Yukun; Ma, Huiyun; Yu, Chenggang; Dong, Liangliang; Yang, Yunshan; Zhu, Xiaohua; Sun, Hanwen
Abstract : Wireless control downhole throttle is designed to control the opening of downhole throttle remotely by ground pressure wave signal to regulate downhole production in a wireless and intelligent manner. The throttle's production regulation capability and the noise immunity of the signal receiver are the key factors affecting the reliability of the throttle operation. Based on computational fluid dynamics (CFD) theory, the flow field of downhole throttle is simulated numerically to study the flow resistance characteristics of wireless control downhole throttle and the stability of flow field at signal receiver. Finally, the field test proves that the tool achieves the design capacity of production regulation and can accurately receive signals to regulate downhole production in a wireless and intelligent manner. The research content of this paper provides theoretical and experimental basis for the further improvement and optimization of the wireless control downhole throttle's structure and has certain guiding significance for the field use of the throttle, achieving the purpose of downhole wireless intelligent production adjustment.